Krzemienne grociki strzał z cmentarzyska ludności kultury mogiłowej w Górzycy nad Odrą - Socha, Krzysztof; Szemelak, Radosław (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The purpose of the paper is a multiaspectual analysis of flint arrowheads from three graves of the Tumulus Culture from the cemetery in Gorzyca (site 20). The analysed assemblage consists of 12 items, mainly made of Cretaceous erratic flint, including two semi-products and ten notched arrowheads. Based on the typological analyses, the assemblage was divided into types.
Flint arrowheads from the cemetery at Górzyca on the Oder River